Polymerization-Induced Phase Segregation and Self-Assembly of Siloxane Additives to Provide Thermoset Coatings with a Defined Surface Topology and Biocidal and Self-Cleaning Properties - Mansouri, Jaleh (Nanomaterials (Basel), 2019)
In this work, we report on the incorporation of a siloxane copolymer additive, poly((2-phenylethyl) methylsiloxane)-co(1-phenylethyl) methylsiloxane)-co-dimethylsiloxane), which is fully soluble at room temperature, in a rapid-cure thermoset polyester coating formulation. The additive undergoes polymerization-induced phase segregation (PIPS) to self-assemble on the coating surface as discrete discoid nanofeatures during the resin cure process. Moreover, the copolymer facilitates surface co-segregation of titanium dioxide pigment microparticulate present in the coating. Depending on the composition, the coatings can display persistent superhydrophobicity and self-cleaning properties and, surprisingly, the titanium dioxide pigmented coatings that include the siloxane copolymer additive display high levels of antibacterial performance against Gram-positive (Staphylococcus aureus) and Gram-negative (Pseudomonas aeruginosa) bacteria. This antibacterial performance is believed to be associated with the unique surface topology of these coatings, which comprise stimuli-responsive discoid nanofeatures. This paper provides details of the surface morphology of the coatings and how these relates to the antimicrobial properties of the coating.